A review of microwave coal processing - Binner, Eleanor; Lester, Edward; Kingman, S.W.; Dodds, Chris; Wu, Tao; Robinson, John P.; Wardle, Peter; Mathews, Jonathan P. (International Microwave Power Institute, 2014)
This paper reviews the application of microwave energy in coal processing and utilisation. It covers a wide variety of processes including liberation of minerals, coal drying, pre-treatment to improve grindability, liquefaction enhancements and coke making. There is also consideration of analytical techniques that use microwave energy for continuous monitoring of coal feed systems. Where possible, industrial or pilot scale examples of these processes are discussed, along with a consideration of the significant hurdles that exist scaling from bench or pilot scale systems to industrial sized units. The processes with more immediate promise for scale-up are identified, as are those that require further laboratory scale experiments to establish whether microwave processing should be pursued at a larger scale. The importance of dielectric properties of the materials to be processed is emphasised, and the reasons behind the need for a multi-disciplinary approach to the design and operation of electromagnetic experiments are explained. Microwave coal processing is a diverse area, which has the potential to aid in coal upgrading, cleaning and comminution, thus improving efficiency and reducing harmful emissions of coal usage. Other promising research areas include the investigation of microwave processing for coking, liquefaction, enhancing fluid flow in coal beds and coal characterisation. However, due to the scale of most industrial coal processing systems and the lack of availability of microwave hardware at power levels of above 100 kW, commercial applications of microwaves for coal processing are still some if not many years away. Whilst there are some interesting applications from a scientific point of view, a very strong value proposition coupled with an organisation with high acceptance of risk would be required to develop high power microwave equipment able to work effectively in dirty, harsh environments.